2021
DOI: 10.3389/fimmu.2021.696415
|View full text |Cite
|
Sign up to set email alerts
|

IFNγ and iNOS-Mediated Alterations in the Bone Marrow and Thymus and Its Impact on Mycobacterium avium-Induced Thymic Atrophy

Abstract: Disseminated infection with the high virulence strain of Mycobacterium avium 25291 leads to progressive thymic atrophy. We previously showed that M. avium-induced thymic atrophy results from increased glucocorticoid levels that synergize with nitric oxide (NO) produced by interferon gamma (IFNγ) activated macrophages. Where and how these mediators act is not understood. We hypothesized that IFNγ and NO promote thymic atrophy through their effects on bone marrow (BM) T cell precursors and T cell differentiation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…Several mechanisms have been shown to influence thymic atrophy for pathogenic infection such as NK-cell activation, increased levels of glucocorticoids as well as heightened IFN-γ secretion by the thymocytes [9,14,23]. Previously studies have shown that pathogenic infections cause thymic atrophy associated with apoptosis of thymocytes which could be mediated by IFN-γ induced tissue injury [9,11,29]. Our data shows that SARS-CoV-2 infection results in profound elevation (∼five-fold) of IFN-γ by CD45 + cells and to a lesser extent (∼two-fold) by CD45 − cells (Fig.…”
Section: Sars-cov-2 Infection Induces Thymic Atrophy and Leads To Dys...mentioning
confidence: 99%
“…Several mechanisms have been shown to influence thymic atrophy for pathogenic infection such as NK-cell activation, increased levels of glucocorticoids as well as heightened IFN-γ secretion by the thymocytes [9,14,23]. Previously studies have shown that pathogenic infections cause thymic atrophy associated with apoptosis of thymocytes which could be mediated by IFN-γ induced tissue injury [9,11,29]. Our data shows that SARS-CoV-2 infection results in profound elevation (∼five-fold) of IFN-γ by CD45 + cells and to a lesser extent (∼two-fold) by CD45 − cells (Fig.…”
Section: Sars-cov-2 Infection Induces Thymic Atrophy and Leads To Dys...mentioning
confidence: 99%
“…Recent studies have shown that high mortality (more than 25%) is associated with MAC pulmonary disease [55]. Mouse models of M. avium infection elicit an IFN-g response but not an IFN-a response [56], which is specifically dependent on IFNg-induced activation of macrophages [57]. Studies on mice infected with M. avium have shown expansion of Lin-c-kit + Sca-1 + (LSK) cells and that intravenous injection of M. avium causes expansion of Lin-ckit + Sca-1 + , CD34 + , Flk2 À (ST-HSC) cells 4 weeks after the infection [56,58].…”
Section: Models Of Infectionmentioning
confidence: 99%